2019
DOI: 10.3390/ma12010185
|View full text |Cite
|
Sign up to set email alerts
|

Control over the Percentage, Shape and Size of the Graphite Particles in Martensitic White Castings Alloyed with Cr, Nb and Mg

Abstract: This paper presents the results obtained regarding the control by manufacturers of the percentage, shape, and size of the precipitated graphite in the working layer of duplex work-rolls used in hot strip mill finishing stands. This working layer is manufactured in a martensitic white cast iron alloyed with Cr and Nb to promote the precipitation of M3C and MC carbides, which provide a high wear resistance. The thermal cycling behavior of this layer also has a decisive influence on its service life. In this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In this case, it is verified that this effect also reaches the region of the shell in contact with the core. In previous studies by the authors, it was similarly found that if the ladle is not inoculated with FeSi-La, then there is an improvement in the impact toughness inside the working layer [29,30,32]. In the present study, we have verified that this effect is maintained in the region of the shell-core bond.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this case, it is verified that this effect also reaches the region of the shell in contact with the core. In previous studies by the authors, it was similarly found that if the ladle is not inoculated with FeSi-La, then there is an improvement in the impact toughness inside the working layer [29,30,32]. In the present study, we have verified that this effect is maintained in the region of the shell-core bond.…”
Section: Resultssupporting
confidence: 86%
“…The analyzed factors were: The use of FeSi alloy inoculants with traces of lanthanum; inoculation with different percentages of SiCaMn, FeB, and Mg; the percentage of Si; and the liquidus temperature. Previous studies by the authors have analyzed the influence of these factors on the mechanical and microstructural properties of the working layers [29,30]. The present paper analyzes their effect on the shell-core bond interface in work rolls.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, it was shown that, with effective quantities of Mg (around 0.02%), a deterioration in the nodularity of the graphite was produced [23]. This same effect was observed with the inoculation of FeB [23]. In previous works, the properties of the working layer were characterized.…”
Section: Introductionmentioning
confidence: 71%
“…These carbides exhibit true continuity in the microstructure; thus, they become the true mechanical matrix [20]. Inoculation with La produces an increase in the number of beads, by unit area, of graphite, and the thinning of the carbide network [21][22][23]. B has a whitening effect, thus increasing the volume fraction of carbides and improving the resistance to wear of the material [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation